2009
DOI: 10.4049/jimmunol.0802810
|View full text |Cite
|
Sign up to set email alerts
|

IL-22-Dependent Attenuation of T Cell-Dependent (ConA) Hepatitis in Herpes Virus Entry Mediator Deficiency

Abstract: Coinhibitors and costimulators control intrahepatic T cell responses that trigger acute hepatitis. We used the ConA-induced hepatitis model in the mouse to test if the coinhibitor herpes virus entry mediator (HVEM) modulates hepatitis-inducing T cell responses. Compared with ConA-injected, wild-type (wt) C57BL/6 (B6) mice, HVEM-deficient (HVEM−/−) B6 mice showed lower serum transaminase levels and lower proinflammatory IFN-γ, but higher protective IL-22 serum levels and an attenuated liver histopathology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…1A). As reported previously [32], serum AST and ALT activities in WT mice peaked at around 12 h after Con A injection, and p19-deficient mice showed similar time kinetics but with enhanced activities compared with WT mice (Fig. 1B).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1A). As reported previously [32], serum AST and ALT activities in WT mice peaked at around 12 h after Con A injection, and p19-deficient mice showed similar time kinetics but with enhanced activities compared with WT mice (Fig. 1B).…”
Section: Resultssupporting
confidence: 86%
“…Increased susceptibility of IL-23p19-deficient mice to Con A-induced hepatitis Since NKT cells play a critical role in Con A-induced hepatitis and are the main producer of the hepatoprotective cytokine IL-22 [32], we first examined T-and NKT-cell populations in liver mononuclear cells (MNCs) of WT-and IL-23p19-deficient mice. Consistent with a previous report that p19-deficient mice have no overt phenotype in thymocytes, splenocytes or peripheral blood leukocytes [33], the populations of NKT, NK and T cells were not impaired in liver MNCs as observed in the splenocytes of p19-deficient mice compared with those of WT mice without any treatment and 5 h after Con A injection (Supporting Information Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because HVEM is expressed by most cells of the immune system (T cells, B cells, NK cells, dendritic cells, and monocytes) and by some nonimmune cells such as hepatocytes, the specific cell subtypes that function as APC in this model were not strictly defined. However, because intrahepatic dendritic cells express HVEM on the surface and NKT maturation in the Con A model requires IL-12, these professional APC are an attractive candidate (54). In addition to professional APC, it is suggested that liver sinusoidal cells could play a role in NKT cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Liver NKT cells can be locally activated either specifically through the TCR (e.g., by glycolipid-presenting cells) or nonspecifically through cytokines such as IL-12 or IL-18 (54). In vivo, activation of T cells is an APC-dependent process, but the APC type that presents the lectin in the liver in this model is not defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation